Flexible and flame-retarding phosphorylated MXene/polypropylene composites for efficient electromagnetic interference shielding. (1st June 2022) - Tang, Tingting; Wang, Shanchi; Jiang, Yue; Xu, Zhiguang; Chen, Yu; Peng, Tianshu; Khan, Fawad; Feng, Jiabing; Song, Pingan; Zhao, Yan
Highlights: MXene/PP composites are prepared by hot-pressing PP non-woven fabric coated with functionalized MXene. The final composite exhibits an EMI shielding performance of ∼90 dB (8–12 GHz, thickness ∼400 μm). The resultant MXene/PP composites are mechanically robust with a superior anti-fatigue capability. The resultant MXene/PP composites exhibit a self-extinguishing capability. Abstract: Flame-retardant composites with high electromagnetic interference (EMI) shielding performance are desirable for electronic device packaging. Despite great potential of MXene for high EMI, it still remains a great challenge to develop high-performance flame-retardant polymer/MXene composites with excellent EMI shielding effectiveness because of the poor oxidative stability of MXene. Herein, phosphorylated MXene/polypropylene (PP) composites are prepared by coating phosphorylated MXene on PP fabric followed by spraying polyethylenimine (PEI) and hot-pressing. The phosphorylated MXene proves to be more durable against oxidation than pure MXene due to the protection effect of polyphosphates. Upon hot-pressing, melted PP fibers are fused together at their contact points and thus as-prepared composites are bi-continuous with two interpenetrating phases. The composites show significantly improved thermal stability and flame retardancy relative to pure PP, with a low total heat release (THR) of 3.7 kJ/g and a heat release rate (HRR) of 50.0 W/g, which are reduced by 78% and 87%, respectively. In addition, the composites exhibit a high electrical conductivity of ∼36, 700 S/m and an EMI shielding performance of ∼90 dB over the whole frequency range of 8–12 GHz with a thickness of ∼400 μm. The as-developed PP/MXene composites hold great promise for reliable protection of next-generation electronic devices working in complex environments.